2018
DOI: 10.1155/2018/1623957
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nivolumab in a Patient with Metastatic Renal Cell Carcinoma and End-Stage Renal Disease on Dialysis: Case Report and Literature Review

Abstract: Treatment of patients with metastatic renal cell carcinoma (mRCC) and end-stage renal disease (ESRD) on dialysis poses a therapeutic challenge, particularly as this patient group was excluded from the pivotal clinical trials. In addition, there is uncertainty regarding drug dosing/pharmacokinetics, lack of safety and efficacy data, and potential for increased toxicity when using targeted therapy or immunotherapy for the management of patients with mRCC on dialysis. Nivolumab, an anti-programmed death-1 immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…3 Currently, there are few published cases of ICI use in patients receiving dialysis. [4][5][6][7] We aimed to characterize cancer response rates and the incidence of overall and severe (grade 3/4) irAEs in nonselected patients undergoing dialysis receiving ICIs at Partners Healthcare.…”
Section: Safety and Efficacy Of Immune Checkpoint Inhibitors In Patiementioning
confidence: 99%
“…3 Currently, there are few published cases of ICI use in patients receiving dialysis. [4][5][6][7] We aimed to characterize cancer response rates and the incidence of overall and severe (grade 3/4) irAEs in nonselected patients undergoing dialysis receiving ICIs at Partners Healthcare.…”
Section: Safety and Efficacy Of Immune Checkpoint Inhibitors In Patiementioning
confidence: 99%
“…Few case reports have reported the successful administration of anti-PD-1 antibodies in cancer patients receiving HD. [11][12][13] Here, we present a patient on HD who achieved complete remission after one dose of the anti-PD-1 antibody pembrolizumab, without severe adverse events. Renal impairment reportedly has little effect on the pharmacokinetics of pembrolizumab.…”
Section: Discussionmentioning
confidence: 97%
“…Current evidence about the efficacy and safety of nivolumab in met-astatic RCC patients on dialysis is very scarce, limited to three case reports ( Table 1). None of them suffered significant toxicities (grade 2-4), and two patients showed clinical benefit [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the exclusion of these patients from the pivotal clinical trials of these drugs. [6] Pharmacokinetic studies found that renal dysfunction did not affect nivolumab clearance, and the EMA (European Medicines Agency) does not recommend dose reductions for chronic kidney disease. As nivolumab is an immunoglobulin G4 with high molecular weight, it is very probably not cleared by dialysis [7].…”
Section: Discussionmentioning
confidence: 99%